2015
DOI: 10.1016/s0140-6736(14)62114-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk attributable to high and low ambient temperature: a multicountry observational study

Abstract: SummaryBackgroundAlthough studies have provided estimates of premature deaths attributable to either heat or cold in selected countries, none has so far offered a systematic assessment across the whole temperature range in populations exposed to different climates. We aimed to quantify the total mortality burden attributable to non-optimum ambient temperature, and the relative contributions from heat and cold and from moderate and extreme temperatures.MethodsWe collected data for 384 locations in Australia, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

113
1,584
15
35

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 2,027 publications
(1,853 citation statements)
references
References 28 publications
113
1,584
15
35
Order By: Relevance
“…Globally, numerous studies have reported that the temperature-mortality relationship tends to follow U-, V-, and J-shaped non-linear patterns, whereby risks in the extreme ends constitute higher risks relative to the minimum mortality temperature (MMT) [15]. These extreme temperatures account for greater risks, and to a certain extent, when analyzed separately, in relation to duration and intensity, which are the length of day and threshold temperature, respectively, constitute the notion of heat waves (HW) [610].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, numerous studies have reported that the temperature-mortality relationship tends to follow U-, V-, and J-shaped non-linear patterns, whereby risks in the extreme ends constitute higher risks relative to the minimum mortality temperature (MMT) [15]. These extreme temperatures account for greater risks, and to a certain extent, when analyzed separately, in relation to duration and intensity, which are the length of day and threshold temperature, respectively, constitute the notion of heat waves (HW) [610].…”
Section: Introductionmentioning
confidence: 99%
“…As was already mentioned, this study used a set of R routines developed and presented by other authors and accompanied to their published papers [1][2]. The analysis is done with R software (version 3.2.4) using the packages dlnm and mvmeta [1][2].…”
Section: Statisticsmentioning
confidence: 99%
“…The analysis is done with R software (version 3.2.4) using the packages dlnm and mvmeta [1][2]. The corresponding codes used in this analysis, were retrieved from the personal website [5] of the first author of the publications [1][2].…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results, the temperature is responsible for increasing a considerable proportion of deaths to 7.71% (95% CI 7.43-7.91). Nevertheless, there are significant inter-country variations in attributable risk (for both hot and cold), with the uppermost attributable risk in Italy, China, and Japan and the lowermost estimates in Thailand, Brazil, and Sweden (Gasparrini et al, 2015).…”
Section: Urban Heat Islandmentioning
confidence: 99%